Recent advancements and challenges of Internet of Things in smart agriculture: A survey - Sinha, Bam Bahadur; Dhanalakshmi, R. (Future generation computer systems, 2022)
The Internet of Things (IoT) is an evolving paradigm that seeks to connect different smart physical components for multi-domain modernization. To automatically manage and track agricultural lands with minimal human intervention, numerous IoT-based frameworks have been introduced. This paper presents a rigorous discussion on the major components, new technologies, security issues, challenges and future trends involved in the agriculture domain. An in-depth report on recent advancements has been covered in this paper. The goal of this survey is to help potential researchers detect relevant IoT problems and, based on the application requirements, adopt suitable technologies. Furthermore, the significance of IoT and Data Analytics for smart agriculture has been highlighted. •Core components and significant technologies used by IoT-based smart agriculture.•Sensors, application domains, software, and hardware of IoT-based smart agriculture.•Security concern, and other challenges of using IoT components in smart agriculture.•Future direction to address the research challenges in smart agriculture.